Adjunctive misoprostol for prevention of post-partum haemorrhage: a pragmatic strategy of selective sequential administration - Mishra, Nalini; Nekkanti, Lalitha Priya; Barma, Poulami; Mishra, Ishan; Mishra, Ishan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To evaluate the effect of adjunctive misoprostol in preventing postpartum haemorrhage (PPH) by selective administration above threshold bleeding in order to reduce its side effects in comparison with primary prevention with oxytocin alone. Methods: It was a prospective observational cohort study conducted at Government medical College of central India. Population included 500 low risk women delivering vaginally. After having received oxytocin as primary prevention, women were monitored for bleeding by quantitative assessment of blood loss (QBL) using an innovative drape (kept prepared at the point of care) and once bleeding crossed 350 ml mark, alternate women were given 800 µg misoprostol sublingually as an adjuvant (study group) and compared with those who did not receive adjuvant misoprostol (control group). Main outcome measure: Comparing the incidence of PPH and side effects between study and control group. Results: 150 women had blood loss >350 ml which constituted 76 women in study and control group each. Incidence of PPH was significantly less in the study group (10.52 versus 22.36%, p<0.05, RR 0.470 95% CI= 0.216-1.024). Though side effects were more (38.15%) in study group but these were mild in nature and when the number was extrapolated to all recruited women, the incidence came down to 11.6%. Conclusions: Sequential adjuvant misoprostol at 350 ml blood loss after primary prevention with oxytocin is an effective and pragmatic strategy for preventing PPH when compared to oxytocin alone but with reduced overall side effects owing to less number of women receiving misoprostol.